Crossing ethnic borders in Malaysia measuring the fluidity of ethnic identity and group formation - Mansor Mohd Noor (Universiti Kebangsaan Malaysia, 1999)
Scholar studying ethnic and race relations often locate the question of identity and group formation as given and unaltered (Geertz 1963) while Barth (1969), Banton (1983) and Shamsul (1996) have been arguing that no group maintains itself. This article belongs to the latter academic tradition in trying also the micro levels; it analyses both the group and individual alignments, as well as the authority-defined and the everyday defined identities. Data colleted from five studies carried out in the Klang Valley and Penang between 1990 and 1988 is utilised to show that universalistic norms of self interest over-ride the concern for ethnic preference. Respondents show that they share some common values and their interactions cross ethnic borders. Pluralism is an accepted social reality in Malaysia and ehnicity is secondary rather than primary.